Standard Operating Procedure (SOP) for seed processing, seed inventory and management in cassava - Bakare, D.; Peteti, P.; Iluebbey, P.; Archibong, J.; John, J.; Udoh, A.; Cliff, M.; Kulakow, P. (International Institute of Tropical Agriculture, 2024)
Cassava is primarily grown via stem cuttings (stakes?), but can also be propagated by seeds. Seed propagation is important to create novel gene combinations and superior cassava varieties. In cassava breeding, "seed processing" refers to the process of preparing harvested seeds, also known as "botanical seed," for sowing, distribution or storage while maintaining their viability and vigor.